Evaluation of a Lipopolysaccharide and Resiquimod Combination as an Adjuvant with Inactivated Newcastle Disease Virus Vaccine in Chickens - Bal Krishan Sharma; Saravanan Ramakrishnan; Abinaya Kaliappan; Mithilesh Singh; Ajay Kumar; Satyabrata Dandapat; Sohini Dey; Madhan Mohan Chellappa (Vaccines, 2022)
Various toll-like receptor (TLR) agonists have shown potential as adjuvants with different vaccines in both human and livestock species, including chickens. Our previous studies on combination of lipopolysaccharide (LPS; TLR4 agonist) and resiquimod (R-848; TLR7 agonist) showed the synergistic up-regulation of pro-inflammatory Th1 and Th2 cytokines in chicken peripheral blood mononuclear cells (PMBCs). Hence, the present study aimed to explore the combined adjuvant effect of LPS and R-848 with inactivated Newcastle disease virus (NDV) vaccine in chickens. Two weeks-old SPF chickens were immunized with inactivated NDV vaccine along with a combination of LPS and R-848 as an adjuvant with suitable control groups. A booster dose was given two weeks later. Antibody responses were assessed by enzyme linked immunosorbent assay (ELISA) and hemagglutination inhibition (HI) test, while cell-mediated immune responses were analyzed by a lymphocyte transformation test (LTT) and flow cytometry following vaccination. Two weeks post-booster, the birds were challenged with a velogenic strain of NDV, and protection against clinical signs, mortality and virus shedding was analyzed. The results indicated that inactivated NDV vaccine with R-848 induced significantly higher humoral and cellular immune responses with 100% protection against mortality and viral shedding following a virulent NDV challenge. However, the combination of LPS and R-848 along with inactivated NDV vaccine produced poor humoral and cellular immune responses and could not afford protection against challenge infection and virus shedding when compared to the vaccine-alone group, indicating the deleterious effects of the combination on antigen-specific immune responses. In conclusion, the combination of LPS and R-848 showed the inhibitory effects on antigen-specific humoral, cellular and protective immune responses when used as an adjuvant with inactivated NDV vaccines in chickens. This inhibitory effect might have occurred due to systemic cytokine storm. A nanoparticle-based delivery of the combination of LPS and R-848 for slow and sustained release could be tried as an alternative method to explore the synergistic effect of the combination as an adjuvant in chickens.